2015
DOI: 10.3168/jds.2014-8137
|View full text |Cite
|
Sign up to set email alerts
|

Bovine chromosomal regions affecting rheological traits in acid-induced skim milk gels

Abstract: The production of fermented milk products has increased worldwide during the last decade and is expected to continue to increase during the coming decade. The quality of these products may be optimized through breeding practices; however, the relations between cow genetics and technological properties of acid milk gels are not fully known. Therefore, the aim of this study was to identify chromosomal regions affecting acid-induced coagulation properties and possible candidate genes. Skim milk samples from 377 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Several studies have detected a major QTL on BTA6 associated with milk protein composition located around the casein cluster (Schopen et al, 2009(Schopen et al, , 2011Huang et al, 2012;Gambra et al, 2013) as well as associations to milk coagulation traits (Gregersen et al, 2014;Glantz et al, 2015). In our study, we have detected a major locus comprising SNP in close proximity to CSN3 (Fig.…”
Section: Identification Of Possible Candidate Genessupporting
confidence: 66%
“…Several studies have detected a major QTL on BTA6 associated with milk protein composition located around the casein cluster (Schopen et al, 2009(Schopen et al, , 2011Huang et al, 2012;Gambra et al, 2013) as well as associations to milk coagulation traits (Gregersen et al, 2014;Glantz et al, 2015). In our study, we have detected a major locus comprising SNP in close proximity to CSN3 (Fig.…”
Section: Identification Of Possible Candidate Genessupporting
confidence: 66%
“…3 and Supplementary Figure S2 ). These loci included DGAT1 (chromosome, chr14, 1.8 M+) 28 , SDC2 (chr14, 69 M+) 15 , GHR (chr20, 31 M+) 15 , CSN2 (chr6, 87 M+) 15 , MGST1 (chr5, 93 M+) 15 , 25 , PAEP (chr11, 103 M+) 30 and GPAT4 (chr27, 36 M+) 29 . The significance peak on chr18, 57 M+, detected in our study overlapped with reported CTU1 locus associated with calving difficulty 27 .…”
Section: Resultsmentioning
confidence: 99%
“…1b ). Variants within CSN3 have long been found to be associated with milk traits [ 34 , 35 ] but only recently have putative causal variants been prioritised [ 25 ]. The milk cell sQTL Chr6:87392580 had perfect linkage disequilibrium ( r = 1) with the variant Chr6:87390576 which has been suggested as a putative causal variant for effects on milk protein yield and percentage [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%